High-Throughput Mass Spectrometric Analysis of the Whole Proteome and Secretome From Sinorhizobium fredii Strains CCBAU25509 and CCBAU45436 - Rehman, Hafiz Mamoon; Cheung, Wai-Lun; Wong, Kwong-Sen; Xie, Min; Luk, Ching-Yee; Wong, Fuk-Ling; Li, Man-Wah; Tsai, Sau-Na; To, Wing-Ting; Chan, Lok-Yi; Lam, Hon-Ming (Frontiers in Microbiology, 2019)
Sinorhizobium fredii is a dominant rhizobium on alkaline-saline land that can induce nitrogen-fixing symbiotic root nodules in soybean. Two S. fredii strains, CCBAU25509 and CCBAU45436, were used in this study to facilitate in-depth analyses of this species and its interactions with soybean. We have previously completed the full assembly of the genomes and detailed transcriptomic analyses for these two S. fredii strains, CCBAU25509 and CCBAU45436, that exhibit differential compatibility toward some soybean hosts. In this work, we performed high-throughput Orbitrap analyses of the whole proteomes and secretomes of CCBAU25509 and CCBAU45436 at different growth stages. Our proteomic data cover coding sequences in the chromosome, chromid, symbiotic plasmid, and other accessory plasmids. In general, we found higher levels of protein expression by genes in the chromosomal genome, whereas proteins encoded by the symbiotic plasmid were differentially accumulated in bacteroids. We identified secreted proteins from the extracellular medium, including seven and eight Nodulation Outer Proteins (Nops) encoded by the symbiotic plasmid of CCBAU25509 and CCBAU45436, respectively. Differential host restriction of CCBAU25509 and CCBAU45436 is regulated by the allelic type of the soybean Rj2(Rfg1) protein. Using sequencing data from this work and available in public databases, our analysis confirmed that the soybean Rj2(Rfg1) protein has 3 major allelic types (Rj2/rfg1, rj2/Rfg1, rj2/rfg1) that determine the host restriction of some Bradyrhizobium diazoefficiens and S. fredii strains. A mutant defective in the type 3 protein secretion system (T3SS) in CCBAU25509 allowed this strain to nodulate otherwise-incompatible soybeans carrying the rj2/Rfg1 allelic type, probably by disrupting Nops secretion. The allelic forms of NopP and NopI in S. fredii might be associated with the restriction imposed by Rfg1. By swapping the NopP between CCBAU25509 and CCBAU45436, we found that only the strains carrying NopP from CCBAU45436 could nodulate soybeans carrying the rj2/Rfg1 allelic type. However, no direct interaction between either forms of NopP and Rfg1 could be observed.